ChemInform Abstract: Two Novel Polycyclic Spiro Lignans from Gymnotheca involucrata. Issue 17 (April 2015) - Xiao, Shi‐Ji; Lei, Xin‐Xiang; Xia, Bing; Xu, Dan‐Qing; Xiao, Hong‐Ping; Xu, Hong‐Xi; Chen, Fang; Ding, Li‐Sheng; Zhou, Yan
Abstract Evaluation of the antiviral activity of gymnothespirolignans A (I) and (II) reveals promising activities.